2000
DOI: 10.1523/jneurosci.20-02-00783.2000
|View full text |Cite
|
Sign up to set email alerts
|

The M1 Muscarinic Agonist CI-1017 Facilitates Trace Eyeblink Conditioning in Aging Rabbits and Increases the Excitability of CA1 Pyramidal Neurons

Abstract: The M1 muscarinic agonist CI-1017 was administered intravenously to aging rabbits on a daily basis before and during hippocampally dependent trace eyeblink conditioning sessions. Circulating levels of CI-1017 were significantly related to the drug dose. The drug was found to significantly increase the rate and amount of learning in a dose-dependent manner with no significant effects on the amplitude, area, or latency of conditioned responses. There was no evidence of pseudoconditioning at the highest drug conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 73 publications
4
52
0
Order By: Relevance
“…It has been reported that mAChR agonists cause depolarization of hippocampal CA1 pyramidal neurons through activation of M 1 mAChRs (Weiss et al, 2000). Indeed, in rat hippocampal slices, carbachol induced pirenzepine-sensitive single-unit firing in the CA1 region, suggesting that it produced its response through activation of M 1 mAChRs.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that mAChR agonists cause depolarization of hippocampal CA1 pyramidal neurons through activation of M 1 mAChRs (Weiss et al, 2000). Indeed, in rat hippocampal slices, carbachol induced pirenzepine-sensitive single-unit firing in the CA1 region, suggesting that it produced its response through activation of M 1 mAChRs.…”
Section: Discussionmentioning
confidence: 92%
“…Acquisition of either trace EBC (rats and rabbits) or WMZ (rats) results in a reduction of the post-burst AHP in CA1 pyramidal neurons (Moyer Jr. et al 1996;Oh et al 2003;Kuo et al 2004). In addition, systemic administration of compounds that reduce the AHP result in an enhancement of learning hippocampus-dependent tasks (Kronforst-Collins et al 1997;Weiss et al 2000). Based on these findings, we hypothesized that training rats on two hippocampus-dependent tasks would result in facilitation of the second task.…”
Section: Discussionmentioning
confidence: 99%
“…Increased evidence also suggests that ERK1/2 activation may be necessary for associated memories in the mammalian nervous system. In addition, recent studies have shown that M 1 agonists ameliorate age-related learning and memory impairments, suggesting that M 1 agonists may be an effective therapy for reducing the cognitive deficits that accompany normal aging and/or Alzheimer's disease (53). Therefore, it is interesting to consider that failure of tyrosine phosphorylation of G␣ q/11 , uncoupling of the receptor-G protein-effector, and a defect in ERK1/2 activation by mAChR observed in the current study may be involved in the early stage of impairment of learning and memory function after cerebral ischemia.…”
Section: Resultsmentioning
confidence: 99%